Q-DNA: A Formal Definition of a Canonical Tetra-Stranded Hereditary Polymer Beyond the Double Helix - Barack Ndenga (Publisher, 2025)
DNA’s canonical double helix remains the dominant genetic architecture in known biology, yet non-canonical nucleic acid structures—such as G-quadruplexes and i-motifs—demonstrate that nucleic acids can access higher-order multistranded conformations in vitro and in vivo. In this paper, I introduce Q-DNA, defined not as a local quadruplex motif but as a hereditary polymer whose canonical, genome-scale ground state is tetra-stranded. I propose a formal axiomatic framework distinguishing Q-DNA from motif-level quadruplexes (e.g., G-quadruplexes) and specify necessary conditions for canonicality, multi-body recognition rules, topologicaladmissibility, and heredity under bounded copying error. I then outline falsifiable predictions and an experimental roadmap leveraging synthetic genetics and XNA technologies, which have already established that alternative genetic polymers can store and propagate information with engineered enzymes. Keywords: tetra-stranded genome, canonical hereditary state, quadruplex motifs, XNA, synthetic genetics, information theory
Q-DNA is a theoretical framework that defines a canonical tetra-stranded hereditary polymer whose genome-scale ground state is four-stranded, explicitly distinct from motif-level quadruplex structures (e.g., G-quadruplexes) observed as local, context-dependent conformations in duplex genomes. This deposit provides a detailed, high-level manuscript introducing Q-DNA through an axiomatic definition of canonicality, multi-body recognition rules (modeled as multi-strand constraint systems), topological admissibility at genome scale, and heredityvia replication mappings under bounded copying error. The work also outlines falsifiable predictions, exclusion criteria (to separate Q-DNA from local quadruplex motifs), and a research roadmap informed by synthetic genetics and XNA progress toward alternative genetic polymers. Intended audience: theoretical biology, molecular biophysics, synthetic genetics, and astrobiology communities. Resource type: manuscript / conceptual framework, with proposed figures and a structured research program for follow-up studies.